TANTANGAN GURU DALAM MENERAPKAN PEMBELAJARAN JARAK JAUH (PJJ) DI ERA TEKNOLOGI DAN KOMUNIKASI - Yuliansyah, Arief; Agus Setiawan; Rama Wijaya Abdul Rojak; Udin Syaefuddin Sa’ud; Atep Sujana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the challenges faced by teachers in implementing distance learning (PJJ) in the era of technology and communication. This research uses the Systematic Literature Review (SLR) method, referring to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), to examine documents from Google Scholar within the range of 2010 to 2024. The search for journal articles was conducted using Publish or Perish with the keywords "challenges of distance learning in the era of technology and information." The search was limited to 50 articles, from which 17 relevant articles were selected based on the challenges faced by teachers in implementing PJJ.The analysis of these journals revealed several key issues. Firstly, many teachers are not yet proficient in using technology, despite the demands of the fourth industrial revolution for enhanced digital competence to ensure smooth PJJ implementation. Secondly, the availability of supporting infrastructure such as devices, strong internet signals, and sufficient data quotas is crucial for successful PJJ, but economic disparities and infrastructure gaps hinder its implementation. Thirdly, in terms of teaching strategies, media, and methods, many teachers tend to assign numerous tasks rather than deliver content during PJJ. To address these challenges, teachers need to enhance their capabilities by participating in various training programs related to technological and informational developments, ensuring that their teaching materials, methods, and strategies are engaging and digital-ready.